1‐Nitropropane [MAK Value Documentation, 2017]. Issue 1 (30th January 2019) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated the maximum concentration at the workplace (MAK value) for 1‐nitropropane, considering all toxicity endpoints. The critical effects of 1‐nitropropane [108‐03‐2 ] were inflammation and degeneration of the olfactory mucosa and inflammation of the squamous epithelium in rats after 28 or 47 days inhalation. The study yielded a NOAEC of 24 ml/m 3 for local effects. Since 2014, the Commission uses an empirical approach to set MAK values for substances with critical effects on the upper respiratory tract or the eyes. According to this approach, the MAK value for 1‐nitropropane has been lowered from 25 ml/m 3 to a concentration of 2 ml/m 3 . As local effects are critical, the assignment to Peak Limitation Category I is confirmed. The excursion factor of 8 is set as a human volunteer study revealed irritative effects only at considerably higher concentrations. Because there are no studies of teratogenicity, the substance is classified in Pregnancy Risk Group D. Skin contact is expected to contribute significantly to systemic toxicity and 1‐nitropropane is designated with an "H". 1‐Nitropropane is not genotoxic and data for carcinogenicity are lacking. Sensitization is not expected from the limited data.